Dutch Ministry of Infrastructure and Water Management as part of grant M240045 and commissioned to the National Institute for Public Health and the Environment - Voogt, M.; Zandveld, P.; Erbrink, H.; Dinther, D. van; Bulk, P. van den; Kos, G.; Blom, M.; Jonge, D. de; Helmink, H.; Meydam, J.; Visser, J.; Middel, J.; et al. (Elsevier, 2023)
Background and objectives In recent years it has been shown that aircraft emissions are a dominant source of ultrafine particles in the surroundings of airports. However, health effects of long-term (monthly to yearly) exposure to these particles are unknown. As part of an integrated research program into the health risks of ultrafine particles around Schiphol Airport, the applicability of the dispersion model STACKS+ to assess long-term exposure to ultrafine particles from aviation was assessed. Methodology A detailed comparison between modelled and measured particle number concentrations (PNC) due to aircraft emissions was carried out at ten locations in the surroundings of Schiphol Airport during two six-month periods in 2017 and 2018. In order to deduce the contribution of aviation to measured PNC, we applied a fitting method of the sum of the modelled contributions from aviation, the modelled contributions from traffic on main roads and the contributions from outside the study area estimated from the measurements, to the measured total PNC. The analysis yielded scaling factors and uncertainty estimates for each of the main contributions. We then subtracted the estimated background and modelled contributions of road traffic from the total measured PNC and took the remainder as an approximation of the measured contribution from aviation to PNC. We compared it to the modelled contribution from aviation, based on the averaged values for the six-month periods. Results Both six-month averaged modelled and measured PNC due to aircraft emissions (i.e., adjusted for background) showed a large range at the monitoring locations representative for population exposure (from close to zero to 10 000 particles/cm3). Spearman and Pearson correlation coefficients between model and measurement results were high (>0.83). Conclusions The applied approach enabled us to obtain a robust estimate of the contribution of aviation to the measured PNC. The dispersion model is able to determine the spatially varying average concentrations due to aircraft emissions in residential areas over periods of 6 months, allowing for application in epidemiological studies into long-term exposure.